2014
DOI: 10.1063/1.4902998
|View full text |Cite
|
Sign up to set email alerts
|

High conductivity micro-wires in diamond following arbitrary paths

Abstract: FIG. 3. Examples of single wires following spiral and helical paths. Both wires were fabricated with four axially shifted passes of the laser beam. The depth of the helical wire ranged from 10 to 30 lm. The positions of subsequent pillar fabrication are marked in the images. (a) Optical transmission microscope image of the spiral wire. (b) Top view and (c) side view of helical wire. (d) 3D SHG microscope image of the helical wire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 27 publications
2
50
1
Order By: Relevance
“…Indeed, due to the lower density of the sp 2 phase, compared to that of sp 3 , a strong localized stress field is generated within the surrounding pristine diamond, which we show here can act as an optical waveguide. Drawing on previous work demonstrating that a combination of high NA focusing and adaptive optics aberration correction is essential for accurate fabrication of graphitic tracks in diamond 31 , we are able to generate Type III depressed cladding waveguides supporting both polarization states and 3D networks of Type II waveguides. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, due to the lower density of the sp 2 phase, compared to that of sp 3 , a strong localized stress field is generated within the surrounding pristine diamond, which we show here can act as an optical waveguide. Drawing on previous work demonstrating that a combination of high NA focusing and adaptive optics aberration correction is essential for accurate fabrication of graphitic tracks in diamond 31 , we are able to generate Type III depressed cladding waveguides supporting both polarization states and 3D networks of Type II waveguides. …”
mentioning
confidence: 99%
“…The structural modification generated, as identified through Raman microspectroscopy is revealed as graphitic and amorphous sp 2 bonded carbon intermixed with sp 3 bonded diamond 26,27 , while it has recently been shown that, in addition, the NV concentration may be enhanced in nearby regions 28 . When the laser focus is traced through the diamond, a continuous damage track is created which is electrically conductive 29,31 , and has been successfully used for a range of radiation detectors [32][33][34] . Transmission electron microscopy and electron energy loss spectroscopy has been used to study thin slices of the laser-modified area, showing the presence of sub-micrometer patches of sp 2 bonded amorphous carbon, in addition to multiple dislocations of the diamond lattice 30 .…”
mentioning
confidence: 99%
“…However, previous Raman studies revealed only the partial formation of sp 2 bonded graphite within the laser irradiated zones. 14,19,23,24 When using such modifications to create wires, the resultant resistivity varies from 0.02 to 2 X cm, [18][19][20]25,26 with values at least an order of magnitude higher than that for polycrystalline graphite. 27 Similarly, when writing optical waveguides using the stress field generated by modifications in Regime (ii), the propagation losses are significantly lower than those expected from a complete conversion of the irradiated zones to graphite.…”
mentioning
confidence: 99%
“…25 Wires were thus fabricated, and the sample was annealed at 900 C in a nitrogen atmosphere for one hour.…”
mentioning
confidence: 99%
See 1 more Smart Citation